Streittheologie in Tübingen am Anfang des 17. Jahrhunderts: Versuch einer sozialpsychologischen Interpretation - Bubenheimer, Ulrich (Kirchliche Zeitgeschichte, 1994)
Conflicts over theological orthodoxy are often interpreted as the struggles to achieve a psycho-social sense of identity, or as the result of attempts to maintain the group dynamics between in-groups or out-groups. Religious identity can certainly be seen as a part of the collective effort to forge identities through normative characteristics, convictions and patterns of behaviour. This need to find an identity is expressed in every group's desire to maintain its values, relationships and structures. The preservation of the group's identity depends on pressures to conform on its members (the in-group) as well as the rejection of the alienating characteristics of those defined as being outsiders (the out-group). Such a model allows us to claim that throughout history the repeated phenomenon of theological conflicts and the persecution of religious dissidents by the forces of orthodoxy can be explained and compared in terms of social-psychological forces, quite independent of the specific theological contents of the dispute. For example we can look at the theological faculty of Tübingen around 1620, where orthodoxy was being defended by two stalwarts, Theodor Thumm and Lukas Osiander. They were engaged in controversy, on the one hand against the upholders in the Lutheran church of a different interpretation of christology, namely the theologians of Gießen who embraced the doctrine of Kenosis, and on the other hand against the bookseller Eberhard Wild, whose heretical views they attempted to censor and bring to trial. We have records showing that some 80 persons supported Wild in a so-called "Tubingen circle", who adopted a nonconformist piety drawn from the teaching of Johann Arndt and organised themselves in what can be seen as a preliminary form of the conventicle movement. The efforts of the orthodox Tübingen clergy to preserve their theological and church identity by rejecting the influences of their colleagues in Gießen were matched by a determination to bring increased pressure to conform on their own members, as can be seen in the case of Wild. The common element in these two apparently different situations is to be found in socio-psychological factors.